2020
DOI: 10.1002/iub.2410
|View full text |Cite
|
Sign up to set email alerts
|

m6A methyltransferase Wilms' tumor 1‐associated protein facilitates cell proliferation and cisplatin resistance in NK/T cell lymphoma by regulating dual‐specificity phosphatases 6 expression via m6A RNA methylation

Abstract: Nasal-type natural killer/T-cell lymphoma (NKTCL) is an aggressive malignancy with poor survival outcomes that is relatively resistant to chemotherapy. N6-Methyladenosine (m6A) modification, the most prevalent modification of eukaryotic messenger RNA, is involved in the progression of various tumors. However, it is unclear whether it has a physiological role in NKTCL development. To address this question, we probed its function and molecular mechanisms in NKTCL. Initially, we demonstrated that Wilms' tumor 1-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 26 publications
0
36
0
1
Order By: Relevance
“…This remarkable emerging technology provides a solid foundation for the clinical targeting of m 6 A modification in cancer treatment. Furthermore, some preclinical research also found that depletion of some m 6 A regulators can sensitize tumor cells to chemotherapies, including breast cancer and NK/T cell lymphoma 132,133 . Nevertheless, further detailed studies are required to realize its potential.…”
Section: Therapeutic Potential Of Targeting M6a Regulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This remarkable emerging technology provides a solid foundation for the clinical targeting of m 6 A modification in cancer treatment. Furthermore, some preclinical research also found that depletion of some m 6 A regulators can sensitize tumor cells to chemotherapies, including breast cancer and NK/T cell lymphoma 132,133 . Nevertheless, further detailed studies are required to realize its potential.…”
Section: Therapeutic Potential Of Targeting M6a Regulatorsmentioning
confidence: 99%
“…Furthermore, some preclinical research also found that depletion of some m 6 A regulators can sensitize tumor cells to chemotherapies, including breast cancer and NK/T cell lymphoma. 132,133 Nevertheless, further detailed studies are required to realize its potential. Finally, it is notable that m 6 A expression profiles have great potential to differentiate the immune characteristics of patients with tumors, which is likely to accurately guide the application of immunotherapy in clinical.…”
Section: Therapeutic Potential Of Targeting M 6 a Regulatorsmentioning
confidence: 99%
“…WTAP, another MTC component, protects natural killer/T-cell lymphoma (NKTCL) cells from Bax-modulated apoptosis induced by cisplatin (DDP) via regulation of dual-specificity phosphatases 6 (DUSP6). That is, ablation of WTAP augmented the chemosensitivity of NKTCL by decreasing the drug resistance-associated proteins MRP1 and P-gp [ 131 ]. Saikosaponin-d (SsD), an FTO inhibitor, improved the efficacy of nilotinib and PKC412 by reducing FTO-mediated m 6 A hypomethylation and Bcl-2 transcripts in AML-resistant patients [ 137 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to METTL3, WTAP has also been associated with cisplatin resistance. In nasal-type natural killer/T-cell lymphoma (NKTCL), WTAP contributes to cancer progression and chemotherapy sensitivity by stabilizing DUSP6 mRNA in an m6A-dependent manner [ 95 ]. In addition to cisplatin, oxaliplatin is a novel platinum drug that is used to circumvent cisplatin-mediated resistance mechanisms.…”
Section: M6a Methyltransferases In Chemotherapeutic Resistancementioning
confidence: 99%